2022
DOI: 10.26552/com.c.2022.1.a12-a25
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Traffic Parameters on a Section in the City of the National Road during Several Years of Operation

Abstract: The study carried out an analysis of the vehicle traffic parameters on a national road in 2011-2016. The variability and uncertainty of results were evaluated. An analysis of traffic data recorded on the city's entry and exit lanes was carried out. The variations in traffic volume are of interest e.g. in dynamic traffic management systems and navigation services, examining the benefits of flexible work time and places and assessing the environmental effects of traffic congestion. Research has shown that the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The traffic volumes and noise analyzed in this study were measured [12] by the permanent station recording traffic volume, velocity, and sound pressure levels located in Popieluszka Av. in Kielce.…”
Section: Measurements and Calculations Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The traffic volumes and noise analyzed in this study were measured [12] by the permanent station recording traffic volume, velocity, and sound pressure levels located in Popieluszka Av. in Kielce.…”
Section: Measurements and Calculations Resultsmentioning
confidence: 99%
“…Compared to Saturdays on Sundays, both the shape of the speed chart and the speed values at individual hours of the day are different. The analysis of the share of individual groups of vehicles in the traffic structure [12] showed that the dominant group is passenger vehicles, for which the share in the traffic flow was on Sundays 84%. The next group was medium-heavy vehicles, for which the share in the analyzed period amounted on Sundays to 11%.…”
Section: Measurements and Calculations Resultsmentioning
confidence: 99%
See 3 more Smart Citations